HADIS SEBAGAI SUMBER HUKUM ISLAM (Studi Kasus Pandangan Masyarakat Desa Besito-Kudus Terhadap Hadis Larangan Tertawa) - Arim Zufaida Amna (STIS Nahdlatul Ulama Aceh, 2020)
The position of the hadith as a source of Islamic law has become a problematic long debate. The problem with the position of a hadith in society can be seen from the quality of the hadith. This study aims to conduct an analysis of the meanings contained in the laughter hadith and its application in certain societies. This research uses qualitative research methods through literature studies and case studies of the village community of Besito-Kudus to obtain a conclusion. This discussion presents the arguments around the hadith prohibiting laughter as a source of Islamic law in a society. This study concludes that the problems surrounding a hadith position as a basic source of Islamic law in the village community of Besito have generated positive dynamics.